Warped product CR-submanifolds of Sasakian manifolds with respect to certain connections - Shyamal Kumar Hui; Joydeb Roy (Journal of the Indonesian Mathematical Society, 2019)
The present paper deals with the study of warped product CR-submanifolds of Sasakian manifolds with respect to semisymmetric metric and semisymmetric non-metric connection. Among others, Ricci solitons of such notions have been investigated.